Poetics of Peril. Issue 3 (December 2017) - Johannessen, Lene M.
Abstract : From the rich register of ideas in Ranjan Ghosh and J. Hillis Miller's Thinking Literatures across Continents, a few stand out as particularly poignant for the present exploration of literature's work. 'Poetics of Peril' is particularly concerned with the relationship between the dynamism embedded in the understanding of 'presence' as 'absence in process' (Ghosh and Miller 2016 : 122), the idea of the text as 'noise', and the intricate relationship of both of these kinds of 'presencing' to metaphor as 'initiating a kind of change ( phora ), a translocation of meaning, a momentum for the across' (87). A selection of texts comes to mind where the triad of what lies between the 'to be'/the 'not yet', 'noise', and translocation orchestrates the narrative. It can be read for and brought into dialogue across the periods and locations from where the works speak, from William Kentridge's video installation 'More Sweetly Play the Dance' (2015) to Tabish Khair's The Bus Stopped (2004 ) and Herman Melville's 'Benito Cereno' (1855), to Julie Otsuka's The Buddha in the Attic (2011). While very different in provenance, focus, and even genre, the four share certain narrative patterns whose presencing resides in sudden aesthetic ruptures and shifts which ultimately, and most seriously, bespeak epistemological unravelings and dis-placements, a poetics of peril and aesthetic of absence.